A practical hydro, dynamic unit commitment and loading model. - Siu, T.K.
We describe the dynamic unit commitment and loading (DUCL) model that has been developed for use in real-time system operations at BC Hydro (BCH) to determine the optimal hydroelectric unit generation schedules for plants with multiple units and complex hydraulic configurations. The problem is formulated and solved with a novel procedure that incorporates three algorithms. First, an expert system is used to eliminate infeasible and undesirable solutions. Second, dynamic programming is used to solve the optimal static unit commitment problem for a given plant loading, feasible unit combinations, and current hydraulic conditions. Third, the DUCL problem is formulated and solved as a large-scale network problem with side constraints. Output from the model includes DUCL schedules, spinning and operating reserve, and trades curves such as that between water usage and the number of unit switches. The innovative use of the procedure allows the model to effectively schedule hydro units for the energy and capacity markets in real-time. Application of the method is demonstrated by determining the 24-time-step DUCL schedule for a 2700 MW plant with ten units of four different unit types
Keywords: 2700 MW; BC Hydro; Capacity market; Complex hydraulic configurations; Dynamic programming; Dynamic unit commitment and loading model; Energy market; Expert system; Hydraulic conditions; Large-scale network problem; Multiple units; Operating reserve; Optimal hydroelectric unit generation schedules; Optimal static unit commitment; Spinning reserve; Trades curves; Water usage